Respuesta :
on this equation this formula implies: (a2-b2)=(a+b)(a-b)
so the factored form of equation a2-121 will be:
(a+11)(a-11)
hope that helps :)
so the factored form of equation a2-121 will be:
(a+11)(a-11)
hope that helps :)
Answer:
The factored form is given by (a+11)(a-11)
Step-by-step explanation:
We have been given the expression [tex]a^2-121[/tex]
We can write [tex]121=11^2[/tex]
Thus, we have
[tex]a^2-11^2[/tex]
Now, using the formula for difference of squares, which is given by
[tex]a^2-b^2=(a+b)(a-b)[/tex]
On comparing the above expression, with the given formula, we get a=a, b=11. Thus, we have
[tex]a^2-11^2=(a+11)(a-11)[/tex]
Therefore, the factored form is given by (a+11)(a-11)